Gauge/String Duality, Hot QCD and Heavy Ion Collisions - Casalderrey-Solana, Jorge; Liu, Hong; Mateos, David; Rajagopal, Krishna; Achim Wiedemann, Urs (Cambridge University Press, 2023)
Heavy ion collision experiments recreating the quark-gluon plasma that filled the nascent universe have established that it is a nearly perfect liquid that flows with such minimal dissipation that it cannot be seen as made of particles. String theory provides a powerful toolbox for studying matter with such properties. This book provides a comprehensive introduction to gauge/string duality and its applications to the study of the thermal and transport properties of quark-gluon plasma, the dynamics of how it forms, how it flows, and its response to probes including jets and quarkonium mesons. Calculations are discussed in the context of data from RHIC and LHC and results from finite temperature lattice QCD. This is an ideal reference for students and researchers in string theory, quantum field theory, quantum many-body physics, heavy ion physics and lattice QCD.